Empowering scientific thinking skills through creative problem solving with scaffolding learning - Devi Ratnasari; Suciati Suciati; Maridi Maridi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Scientific thinking is a crucial skill for students in facing 21st-century challenges. The aim of this study was to analyze the effect of Creative Problem Solving (CPS) with scaffolding learning implementation on students' thinking skills. The study employed pre-experimental design in which the sample was 96 of population was 270 students. The sampling technique used was cluster random sampling. The data obtained from the test instrument constructed from four aspects observed. The data was analyzed using dependent t-test. The results showed that there was an influence of the CPS with scaffolding on students' scientific thinking skills. Thus, CPS with scaffolding learning effectively empowered the students’ scientific thinking skills.